An update on the efficacy and safety of novel anticoagulants for cancer associated thrombosis. (24th March 2021) - Cosmi, Benilde
ABSTRACT: Introduction : Cancer-associated thrombosis (CAT) refers to the most common thromboembolic complication of cancer which is venous thromboembolism (VTE). CAT primary prophylaxis, treatment, and secondary prevention are challenging for the complexity of cancer patients, who exhibit hypercoagulability with concomitant-heightened bleeding risk. Areas covered : In this review, the author examines the role of low molecular weight heparins (LMWH), which have been the standard of care for CAT treatment for many years. Direct oral anticoagulants (DOACS) have practical advantages over subcutaneous LMWH, especially for long-term therapy. The author then discusses the results of two RCTs which separately compared the direct oral factor Xa inhibitors, apixaban or rivaroxaban, with placebo for CAT prophylaxis in ambulatory high-risk cancer patients and found that DOACS reduced VTE but increased bleeding. Finally, the author discusses four RCTS separately comparing an oral direct factor Xa inhibitor (edoxaban, rivaroxaban, or apixaban) with LMWH for CAT treatment. DOACS showed non-inferior efficacy, although rivaroxaban and edoxaban showed higher bleeding rates, especially in gastrointestinal cancers. Expert opinion : DOACS have a convenient route of administration and do not require laboratory monitoring, although choice of anticoagulants for CAT depends on factors such as tumor type, bleeding risk, concomitant drugs, and comorbidities.